Unraveling methane adsorption mechanisms in tectonically deformed coal: coupling roles of fissure width, deformation degree, and molecular structure - Wang, Lu; Li, Jing; Liu, Guanjun (Frontiers in Earth Science, 2026)
Tectonically deformed coal (TDC) is widely distributed in major coalbed methane (CBM) producing areas in China, and its fissure-like pore structure is a key factor regulating methane adsorption-desorption behavior. To clarify the coupling mechanism of fissure width, tectonic deformation degree, and methane adsorption, three brittle TDC samples with different deformation intensities (Tunlan: weakly deformed, TL; Malan: moderately deformed, ML; Jining: strongly deformed, JN) from the Xishan Coalfield were selected. Fourier Transform Infrared Spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and 13C nuclear magnetic resonance (13C-NMR) were used to characterize molecular structures, and molecular dynamics (MD) simulations were performed to investigate methane adsorption in 2 nm, 5 nm, and 10 nm fissure-like pores under 298 K, 328 K, 358 K, and 0–20 MPa. The results show that fissure width and pressure synergistically regulate adsorption energy distribution. Narrow fissures (2 nm) show multi-peak distribution (molecular crowding effect), while wide fissures (10 nm) exhibit single stable peaks; increasing pressure reduces energy dispersion by 44% (5 nm pore, 5→20 MPa) and enhances adsorption stability. Deformation degree controls adsorption capacity via pore structure evolution. ML (moderate deformation) has the highest capacity (multi-scale pore connectivity), TL (weak deformation) shows limited high-pressure growth (isolated large pores), and JN (strong deformation) has the lowest capacity (fragmented narrow fissures and trap adsorption). A unified “multi-scale pore-fracture synergy adsorption mechanism” is proposed, integrating isolated, synergistic, and trap adsorption as context-dependent manifestations. This study provides a theoretical basis for efficient CBM development in TDC reservoirs by revealing the quantitative coupling relationship between structural factors and methane adsorption.